To all our readers and collaborators, thank you! (Journal of Parents and Teachers, 2013)
The motto of this educational magazine is "a magazine for schools with schools". Consistent with this idea, since the writing of the magazine seeks to create a tool to aid training, fundamentally designed for Catholic centers. This editorial is grateful to all the people who make this possible.
Keywords: Padres y Maestros; educational magazine; thanks to editors; collaborators and readers.